Pneumococcal puerperal mastitis in a lactating mother. Issue 6 (24th April 2019) - Skalidis, T.; Stamnidi, A.; Syriopoulou, V.; Kontopoulos, G.; Legakis, N.
Abstract : Introduction. A case of pneumococcal mastitis in a breast-feeding mother 6 months postpartum is described. Mastitis is usually caused by Staphylococcus aureus . A review of the literature from 1950 to March 2018 revealed only four other cases in which the causative organism was Streptococcus pneumoniae Case presentation. The nursing mother presented with high fever and the four cardinal signs of inflammation of the left breast: calor, dolor, rubor, tumour. In milk culture Streptococcus pneumoniae was isolated in numbers exceeding 10 5  c.f.u. ml −1 . The strain was of polysaccharide serotype 11 not included in Prevnar-13. Susceptibility testing showed full sensitivity to β -lactam antibiotics as well as to macrolides, lincosamides, vancomycin and tetracycline Conclusion. Streptococcus pneumoniae should be considered as a possible causative agent of puerperal mastitis